Teachers' perceptions of using drama- and other action-based methods in language education / Kaisa Hahl and Nely Keinänen - Hahl, Kaisa; Keinänen, Nely (Universiti Teknologi MARA, Kedah, 2021)
This article examines teachers' perceptions of the use of drama- and other action-based methods in teaching a foreign or second language in Finland. Prior research reveals that much foreign language teaching is textbook-based and does not utilize the target language effectively. International research on drama- and action-based methods shows that these instructional techniques are beneficial to student learning and language acquisition. The data for this study were collected through an online questionnaire with closed and open questions and analyzed inductively with content analysis. The findings indicate that a majority of the participants (n=130) used action based methods regularly. Teachers used these methods because they believed they improve student learning, increase motivation, and liven up lessons. However, teachers lacked training in action based methods and some also felt there is no time for these methods in busy schedules. Using drama methods was much less common than other action-based methods, such as different word games with movement. The findings show that although textbooks provide ideas for dramatized reading of texts, teachers found most activities online or made them up themselves. Drama and other action-based methods should be incorporated into teacher education and language textbooks so that teachers would gain confidence and competence in using them and have easy access to different, even more complex activities.